Jumlah Wisatawan, Produk Domestik Regional Bruto dan Jumlah Penduduk Pengaruhnya terhadap Pendapatan Asli Daerah Provinsi Jawa Tengah - Era Siony Kanaan; Widhy Setyowati (Jurnal Ilmiah Aset, 2023)
This research aims to examine the effect of the Number of Tourists, Gross Regional Domestic Product and Total Population on the Regional Original Income of Central Java Province in 2018-2020. The sample in this research were 35 district/cities in Central Java Province. The data used in this study is quantitative secondary data with the Multiple Linear Regression analysis tool model using the SPSS program. The results of this study indicate that the number of tourists has a positive and significant effect on Regional Original Income, GRDP has a positive and significant effect on Regional Original Income. and Total Population has a positive and significant effect on Regional Original Income.